Orçamento público da saúde: um estudo do ciclo orçamentário no município de Maringá - PR - Ribeiro, Roberto Rivelino Martins (2017)
This thesis makes an empirical study about the budget cycle in a municipality, from the inquiry of those responsible for the process, with a view to know in detail how the same occurs throughout its cycle and, therefore, established as objective of the study investigate The Budgetary Cycle of the Health Sector in the Municipality of Maringá, in the period of 2013 and 2014. In order to conduct the research, in terms of an empirical object, the Budgetary Cycle was proposed before the Municipal Health Plan of the Municipality of Maringá, through The accomplishment of a research that, methodologically, fits as being of descriptive nature, of applied form, analyzed qualitatively, with the use of documentary techniques and survey. With regard to the collection of data, public health documents were used, which are composed of the Municipal Health Plan, the Pluriannual Plan, the Budgetary Guidelines Law, the Annual Budget Law and the Annual Management Report, as well as the Semi-structured interview with those responsible for the budget process, analyzed through the technique of content analysis. The findings of the research show that, in relation to the established variables, which, regarding the formation of the responsible, is adequate to the function; Already the elaboration of the budget in operational terms meets the criteria of public planning and it meets the established in the Municipal Plan of Health and Plurianual Plan. Therefore, there is synergy between the elements of planning. Regarding the role of the actors, the study shows that there is an effective participation in the elaboration phase of the budget proposal and that they are diminishing in the other phases of the cycle. Regarding the use of information technology for cycle management purposes, the research demonstrated that there is a satisfactory system. Regarding the review of expenses, the constant realization is close to what is verified in the literature, soon there is effective management of the financial aspects. Finally, in the verification of the autonomy, it was verified that the professional responsible for the budget process has a greater degree of autonomy in front of the other public agents involved.